"Fear, punishment anxiety and the wolfenden report" - "Berg, Charles" (London, 1959)
This book is based on Psychology of Punishment. The fundamental Nature of Anxiety was based on a lecture given to the Psychiatric Discussion Circle at the Cassel Hospital , London.
Keywords: Psychology